ANALISIS KADAR PROTEIN PADA ULAT SAGU (RHYNCHOPHORUS FERRUGINEUS) ASAL KABUPATEN HALMAHERA TIMUR MALUKU UTARA DENGAN METODE KJELDAHL - Widiastuti, Harti; Kisan, Chakrawaty M. (Jurnal Ilmiah As-Syifaa, 2014)
Analysis of Protein Levels In Sago Worm (Rhynchophorus ferrugineus) East Halmahera, North Maluku regency with Kjeldahl Method Has done research on the analysis of protein content in sago (Rhynchophorus ferrugineus) from East Halmahera in North Maluku kjeldahl method. This study aims to obtain scientific data about the protein content in sago (Rhynchophorus ferrugineus).This research includes testing levels  of total nitrogen and non protein nitrogen method kjeldahl on sago(Rhynchophorus ferrugineus). Research results showed that the protein content in sago (Rhynchophorus ferrugineus) Originof East Halmahera in North Maluku is 4.0575 %.Key words : Protein, Ulat Sagu.